Influence of surface characteristics of implant materials on MRSA biofilm formation and effects of antimicrobial treatment - van Dun, Sven C. J.; Verheul, Mariëlle; Pijls, Bart G. C. W.; van Prehn, Joffrey; Scheper, Henk; Galli, Federica; Nibbering, Peter H.; de Boer, Mark G. J. (Frontiers in Microbiology, 2023)
One of the main causes of treatment failure in bacterial prosthetic joint infections (PJI) is biofilm formation. The topography of the biofilm may be associated with susceptibility to antimicrobial treatment. The aims of this study were to assess differences in topography of biofilms on different implant materials and the correlation thereof with susceptibility to antimicrobial treatment. Methicillin-resistant Staphylococcus aureus (MRSA) 7-day mature biofilms were generated on discs made from titanium alloys (Ti-6Al-7Nb and Ti-6Al-4V), synthetic polymer and orthopedic bone cement, commonly used in implant surgery. The surface topography of these implant materials and the biofilms cultured on them was assessed using atomic force microscopy. This provided detailed images, as well as average roughness (Ra) and peak-to-valley roughness (Rt) values in nanometers, of the biofilm and the material surfaces. Bacterial counts within biofilms were assessed microbiologically. Antimicrobial treatment of biofilms was performed by 24-hour exposure to the combination of rifampicin and ciprofloxacin in concentrations of 1-, 5- and 10-times the MBC. Finally, treatment-induced differences in bacterial loads and their correlation with biofilm surface parameters were assessed. The biofilm surfaces on titanium alloys Ti-6Al-7Nb (Ra = 186 nm) and Ti-6Al-4V (Ra = 270 nm) were less rough than those of biofilms on silicone (Ra = 636 nm). The highest roughness was observed for biofilms on orthopedic bone cement with an Ra of 1551 nm. Interestingly, the roughness parameters of the titanium alloys themselves were lower than the value for silicone, whereas the surface of the bone cement was the roughest. Treatment with 1- and 5-times the MBC of antibiotics resulted in inter-material differences in CFU counts, ultimately showing comparable reductions of 2.4-3.0 log CFU/ml at the highest tested concentration. No significant differences in bacterial loads within MRSA biofilms were observed between the various implant materials, upon exposure to increasing concentrations of antibiotics. The surface parameters of MRSA biofilms were determined by those of the implant materials on which they were formed. The antibiotic susceptibility of MRSA biofilms on the various tested implant materials did not differ, indicating that the efficacy of antibiotics was not affected by the roughness of the biofilm.